Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Given the integral equation: $$\sqrt{f(x)}\int_{0}^{x}f(\tau)d\tau=g(x)$$ with g(x) known function, in what cases and how is it possible to solve it?

Thanks

share|improve this question
1  
If $g(x)=k_1x^\beta$ then the solution has a simple form $f(x)=\sqrt{(\alpha+1)k_1} x^\alpha$ being $\alpha=\frac{2}{3}(\beta-1)$ with $\beta\ne 1$. –  Jon May 31 '12 at 14:08

2 Answers 2

up vote 3 down vote accepted

Square both sides of the equation : $$F^'(x) \ (F(x))^2=(g(x))^2$$ with $F(x) = \int_{0}^{x}f(\tau)d\tau $.
Now by integration between 0 and t : $$\frac{(F(t))^3}{3} = \int_{0}^{t} (g(x))^2 dx$$ F(t) can now be expressed : $$F(t) =\sqrt[3]{3} \ \left( \int_{0}^{t} (g(x))^2 dx \right)^{1/3}$$ since $F'(t)=f(t)$, by derivation we obtain : $$f(t) = \sqrt[3]{3} \ (g(t))^2 \left(\int_{0}^{t} (g(x))^2 dx \right)^{-2/3}$$

share|improve this answer

Let us assume that $g(x)$ is differentiable (in fact $g(x)$ should be also positive and monotonously increasing $f(x)$ has to be positive such that the square root is properly defined).

Take a derivative of your equation and you obtain $$ f(x)^{3/2} + \frac{g(x)\, f'(x)}{2 f(x)} =g'(x). $$ Thus, you have reduced your equation to a differential equation with the initial condition $f(0) = g(0)$.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.